1993
DOI: 10.1152/ajpcell.1993.264.2.c361
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of chlorotoxin, a chloride channel ligand from the venom of the scorpion

Abstract: We have previously demonstrated that the venom of the scorpion Leiurus quinquestriatus blocks small-conductance Cl- channels, derived from epithelial cells, when applied to the cytoplasmic surface. We have now purified to near homogeneity, and characterized, the component responsible for this blocking activity. It is a small basic peptide of 4,070 Da. The primary amino acid structure shows considerable homology to a class of previously described putative short insectotoxins. A brief characterization of the kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
285
0
6

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(294 citation statements)
references
References 24 publications
3
285
0
6
Order By: Relevance
“…Thus, the mechanisms by which NPPB and Cltx inhibit Transwell migration differ because NPPB inhibits the function of ClC-3 channes, whereas Cltx depletes functional ClC-3 channels from the membrane. These data indicate a novel action of this scorpion toxin, which was presumed to be a Cl − -channel-specific peptide (DeBin et al, 1993). Rather than acting directly on the ion channel, it appears to interfere with protein trafficking.…”
Section: A Putative CL − Channel Inhibitor (Cltx) Is Currently In Climentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, the mechanisms by which NPPB and Cltx inhibit Transwell migration differ because NPPB inhibits the function of ClC-3 channes, whereas Cltx depletes functional ClC-3 channels from the membrane. These data indicate a novel action of this scorpion toxin, which was presumed to be a Cl − -channel-specific peptide (DeBin et al, 1993). Rather than acting directly on the ion channel, it appears to interfere with protein trafficking.…”
Section: A Putative CL − Channel Inhibitor (Cltx) Is Currently In Climentioning
confidence: 89%
“…Before the molecular characterization of glioma Cl − channels, which we now presume to be primarily ClC-3 channels, we found that Cltx, a scorpion-derived 36-residue peptide that was isolated as a putative Cl − -channel blocker (DeBin et al, 1993) inhibits whole-cell Cl − currents in glioma cells in vitro (Lippiat et al, 1998) and in situ (Ullrich et al, 1998). Moreover, Cltx inhibits glioma-cell invasion in several in situ invasion models, as does the Cl − -channel inhibitor NPPB (Soroceanu et al, 1999).…”
Section: A Putative CL − Channel Inhibitor (Cltx) Is Currently In Climentioning
confidence: 99%
“…Imperatoxin I is a heterodimer (104 and 27 amino acids, respectively) that blocks Ca 2ϩ channel by inhibition of ryanodine binding (9). Scorpion toxins that inhibit Cl Ϫ channels are ϳ36 amino acids long with four disulfide bridges (10,11). Scorpion toxins possess a highly conserved secondary structure arrangement comprising double-or triplestranded antiparallel ␤-sheet and a stretch of ␣-helix maintained by a couple of disulfide bridges (4,12).…”
mentioning
confidence: 99%
“…For instance, snake venoms contain potent neurotoxins that block acetylcholine receptors (3), and snail and spider venoms contain small molecular weight proteins directed against neuronal Ca 2ϩ channels (4,5). A Cl Ϫ channel-specific blocker peptide was also recently isolated from a scorpion venom (6). Thus, there exist a vast array of natural ligands useful for structural and functional characterization of ionic channels.…”
mentioning
confidence: 99%